2008
DOI: 10.1016/j.conb.2008.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Signaling by death receptors in the nervous system

Abstract: SummaryCell death plays an important role both in shaping the developing nervous system and in neurological disease and traumatic injury. In spite of their name, death receptors can trigger either cell death or survival and growth. Recent studies implicate five death receptors -Fas/CD95, TNFR1 (tumor necrosis factor receptor-1), p75 NTR (p75 neurotrophin receptor), DR4 and DR5 (death receptors-4 and -5) -in different aspects of neural development or degeneration. Their roles may be neuroprotective in models of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
63
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 56 publications
2
63
0
1
Order By: Relevance
“…It has been proposed that dependence receptors thus act mainly as amplifiers of low amounts of caspase activity, which yield to efficient cell death through the release of a part of their intracellular domain that is sufficient to convey death signals. In the case of Unc5 receptors, this intracellular domain bears structural similarities to a death domain structural motif, similar to the one found in p75 and other pro-apoptotic receptors (Frade et al 1996;Haase et al 2008;Llambi et al 2001). Surprisingly, however, the intracellular part of DCC that seems to be necessary and sufficient for apoptotic effects does not bear any homology with such domains.…”
Section: Axon Guidance Molecules and Neural Cell Death Netrins And Thmentioning
confidence: 94%
“…It has been proposed that dependence receptors thus act mainly as amplifiers of low amounts of caspase activity, which yield to efficient cell death through the release of a part of their intracellular domain that is sufficient to convey death signals. In the case of Unc5 receptors, this intracellular domain bears structural similarities to a death domain structural motif, similar to the one found in p75 and other pro-apoptotic receptors (Frade et al 1996;Haase et al 2008;Llambi et al 2001). Surprisingly, however, the intracellular part of DCC that seems to be necessary and sufficient for apoptotic effects does not bear any homology with such domains.…”
Section: Axon Guidance Molecules and Neural Cell Death Netrins And Thmentioning
confidence: 94%
“…12 Nerve growth factor in combination with nitric oxide (NO), produced by reactive astrocytes, has been proposed to induce a p75 NTR -dependent motoneuron death in vitro, 13 but conflicting results have not yet demonstrated a functional relevance of p75 NTR in the direct killing of motoneurons in ALS models. 9 We previously demonstrated that Fas triggers a motoneuron-restricted death pathway, which is exacerbated in a cell-autonomous manner by mutant SOD1. 14,15 Interestingly, a functional involvement of the Fas death pathway in motoneuron degeneration in mutant SOD1 mice has been shown.…”
mentioning
confidence: 99%
“…9,10 TNFa can efficiently trigger the death of cultured motoneurons, 11 but may not directly participate to motoneuron degeneration in disease. 12 Nerve growth factor in combination with nitric oxide (NO), produced by reactive astrocytes, has been proposed to induce a p75 NTR -dependent motoneuron death in vitro, 13 but conflicting results have not yet demonstrated a functional relevance of p75 NTR in the direct killing of motoneurons in ALS models.…”
mentioning
confidence: 99%
“…The intracellular region of the p55 tumor necrosis factor receptor, Fas receptor, and p75 contains a death domain sequence (2). The death domain serves as a proteinprotein docking site and is required for initiating tumor necrosis factor-and Fas-mediated apoptosis (3).…”
mentioning
confidence: 99%
“…The p75 receptor is recognized by all the neurotrophins (NGF, 3 brain-derived neurotrophic factor, neurotrophin-3, and neurotrophin-4), which promote differentiation, growth, and survival of diverse cell types in the nervous system (4 -6). Neurotrophins also initiate signaling through Trk tyrosine kinase receptors, which are capable of forming high affinity binding sites with p75 to potentiate responses at low concentrations of neurotrophins (7).…”
mentioning
confidence: 99%